Biomass Estimation of some of the Tropical Pines with Special Reference to Pinus kesiya - Pande, M. C. (Indian Forester, 1987)
The paper summarises the studies conducted in respect of the tropical pines regardiog biomass producction. An atttmpt has been made to furnish the brief details about the biomass studies of Pinus potula. Pinus elliottii and Pinus roxburghli in different localitles in the country. The object has been to compare the total above-ground biomass and of the different components of exotic pines with the indegenous pines. The results of these studies can be made use wherever these pines have given promising results to solve the demand of raw material for paper & pulp. fuel, and firewood requirement of the villages and they can also be put to other variety of uses to ease out the pressure on tbe indegenous species of our natural forests.